PERANAN PROGRAM BURSA KERJA KHUSUS (BKK) DALAM PEMILIHAN KARIR PESERTA DIDIK PADA SEKOLAH KEJURUAN - Indika, Chana; Afdal, Afdal; Hariko, Rizki (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2025)
Abstract: Career decision making is a process of choosing between two or more alternative actions that lead to the choice of majors, professions and certain jobs through career direction exploration by understanding, weighing and making judgments about oneself in relation to the world of work. Making the right career decision is one of the conditions for success in the world of work. Research on career decision making has long attracted the attention of many researchers. Therefore, this study aims to determine the role of the special labor exchange (BKK) in the career selection of students. This research uses the Systematic Literature Review (SLR) research type. Systematic Literature Review is a type of research method by identifying, evaluating, and interpreting research results related to research questions, topics, or certain phenomena of concern. The articles analyzed were selected from databases and google scholar between 2020 and 2023 with the search keywords